The Correlation between Stress Level and Degree of Dysmenorrhea on Female Students at SMA Negeri 1 Surakarta - Mega Aini Rahma; Yulia Lanti Ratna Dewi; Rosalia Sri Hidayati (Nexus Kedokteran Komunitas, 2014)
Backgrounds : Dysmenorrhea is a disorder or menstrual pain in the lower abdomen, buttocks, and spasmodic pain on the medial side of the thigh that may interfere their daily work. One of the risk factors that lead to the occurrence of dysmenorrhea is stress. This study aims to determine the correlation between stress level and degree of dysmenorrhea on female students at SMA Negeri 1 Surakarta. Methods: This study is an observational study with cross sectional approach. This study was conducted in SMA Negeri 1 Surakarta. The sample used was a student who had experienced menstruation, dysmenorrhea and stress, not smoking, not drinking alcohol, not having diseases associated with female reproductive organs, L-MMPI scores with the answer "No" ? 10, and willing to be respondent and approved informed consent. Sampling was done by purposive sampling after selected based on inclusion and exclusion criteria. The dependent variable in this study is the degree of dysmenorrhea, while the independent variable is the level of stress. Research subjects fill (1) the informed consent form and personal data, (2) L-MMPI questionnaire to determine the honesty of respondents in filling out the questionnaire, (3) DASS questionnaire to determine the level of stress, and (4) Questionnaires to determine the degree of dysmenorrhea. Data obtained by 92 research subjects and analyzed using Chi-square test followed by correlation Somers'd. Results : From the analysis of data with numbers of significance ? = 0.05 was obtained value of p = 0.022 (p <0.05) with correlation by 0.238. Conclusions : Statistically, there is a significant association with a weak correlation between stress levels with the degree of dysmenorrhea on female students at SMA Negeri 1 Surakarta. Keywords : Stress level, degree of dysmenorrhea